1983
DOI: 10.1016/0304-3959(83)90071-4
|View full text |Cite
|
Sign up to set email alerts
|

Dental nerve regeneration in rats. I. Electrophysiological studies of molar sensory deficit and recovery

Abstract: Return of sensory nerve function in rat molars following cut or crush injury to the inferior alveolar nerve (IAN) was measured by observing the jaw opening reflex (JOR) response of the digastric muscle to electrical stimulation of individual molars or the gingiva. The IAN was injured from a lateral approach to the mandibular ramus at a site approximately 2 mm proximal to the incisor apex. Following nerve injury, the JOR threshold to stimulation of the first molars increased 6-fold: preoperative threshold mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…This supports the findings from previous studies that have shown more favorable mobilization of immune cells in innervated than denervated pulps after injury (Fristad et al, 1995a), as well as accelerated loss of pulp tissue in denervated than innervated teeth following occlusal exposure (Byers and Taylor, 1993). Rat dental tissues demonstrate almost complete depletion of neurogenic peptides two days after axotomy of the inferior alveolar nerve (Berger et al, 1983), while the first re-innervation processes take place two weeks afterward (Wakisaka et al, 1987;Vandevska-Radunovic et al, 1998). The unchanged number of immunocompetent cells in the denervated and experimentally treated PDL within this period is not an unexpected finding, and is in agreement with previous reports (Fristad et al, 1995b).…”
Section: Morphology and Distribution Of Labeled Immunocompetent Cellssupporting
confidence: 90%
“…This supports the findings from previous studies that have shown more favorable mobilization of immune cells in innervated than denervated pulps after injury (Fristad et al, 1995a), as well as accelerated loss of pulp tissue in denervated than innervated teeth following occlusal exposure (Byers and Taylor, 1993). Rat dental tissues demonstrate almost complete depletion of neurogenic peptides two days after axotomy of the inferior alveolar nerve (Berger et al, 1983), while the first re-innervation processes take place two weeks afterward (Wakisaka et al, 1987;Vandevska-Radunovic et al, 1998). The unchanged number of immunocompetent cells in the denervated and experimentally treated PDL within this period is not an unexpected finding, and is in agreement with previous reports (Fristad et al, 1995b).…”
Section: Morphology and Distribution Of Labeled Immunocompetent Cellssupporting
confidence: 90%
“…Several studies have reported that the reinnervation, tooth sensitivity restoration, and prognosis of the replanted teeth are favored if the tooth infection is controlled with an open apex and rapidly regained revascularization (40)(41)(42). In addition, nerve fibers are known to regenerate after the transection of the inferior alveolar nerve and to grow into the tooth pulp by the sprouting and ingrowth of intact nerves in adjacent tissues (43,44). However, the underlying mechanism of this action needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Resection of the IAN in order to denervate the mandibular teeth in rats has been widely used in studies directed at examining nerve regeneration (Berger and Byers, 1983; Berger et al, 1983; Wakisaka et al, 1987; Takemura et al, 1990; Johnston and Owens, 1991), neural responses to axotomy (Fried et al, 1991; Sasaki et al, 1994; Doubleday and Robinson, 1995; Wakisaka et al, 1996a,1996b; Chudler et al, 1997), responses of dental tissues to denervation (Rehak, 1963; Torneck et al, 1972; Kubota et al, 1985b; Ghassemi‐Tary and Cua‐Benward, 1992; Byers and Taylor, 1993; Fristad et al, 1995; Jacobsen and Heyeraas, 1996, 1997), and central projections of dental afferents (Lapa and Bauer, 1992; Hayama et al, 1993). Strategies for such studies are based partly on the assumption that IAN resection results in axotomy of those neurons that project to the teeth.…”
Section: Discussionmentioning
confidence: 99%
“…For most such studies, the IAN trunk has been injured near its entrance into the mandibular canal with the expectation that this will result in denervation of the mandibular teeth as well as the target tissues of the mental nerve. However, this procedure has been reported to spare the innervation of the 3rd molar and to only partially denervate the 2nd molar (Berger and Byers, 1983; Berger et al, 1983; Jacobsen and Heyeraas, 1996), suggesting that these targets are innervated via alternative pathways that have not been described in morphological accounts of the distribution of the IAN.…”
mentioning
confidence: 98%
See 1 more Smart Citation